Analisis Implementasi Customer Relationship Management dalam Meningkatkan Loyalitas Nasabah pada Koperasi LKMS-A Gapoktan Panampuang Prima - Cici Pramida; Sandra Dewi (Universitas 17 Agustus 1945 Semarang, 2024)
This article is entitled Analysis of the Implementation of Customer Relationship Management in Increasing Customer Loyalty at the LKMS-A Gapoktan Panampuang Prima Cooperative. Matters relating to behavior towards customers, how to serve customers, and all matters relating to customer behavior are part of Customer Relationship Management. In this study, the research used is field research which is descriptive qualitative in nature by collecting data through observation, interviews and documentation. Qualitative research is carried out to build knowledge through understanding and discovery. The results of this research, the implementation of Customer Relationship Management at LKMS-A Gapoktan Panampuang Prima is CRM designed to utilize information technology by developing a continuous relationship with customers by maximizing four dimensions, namely planning, People, Process. , Technology. Which can be seen in the LKMS-A Gapoktan Panampuang Prima which has maximized these four dimensions. Meanwhile, the obstacle faced by the LKMS-A cooperative is the difficulty in increasing the number of customers due to the large number of competing institutions nearby. However, these obstacles can be overcome by improving service quality, increasing trust, increasing satisfaction, and building a better company image.